MgNb2O6 Modified K0.5Na0.5NbO3 Eco‐Piezoceramics: Scalable Processing, Structural Distortion and Complex Impedance at Resonance. Issue 8 (17th August 2021) - Iacomini, Antonio; Garroni, Sebastiano; Senes, Nina; Mulas, Gabriele; Enzo, Stefano; Poddighe, Matteo; García, Álvaro; Bartolomé, José F.; Pardo, Lorena
Abstract: In this work, piezoceramics of the lead‐free composition K0.5 Na0.5 NbO3 with an increasing amount of MgNb2 O6 (0, 0.5, 1, 2 wt.%) were prepared through conventional solid‐state synthesis and sintered in air atmosphere at 1100 °C. The effect of magnesium niobate addition on structure, microstructure and piezoelectric properties was evaluated. The ceramics maintain the orthorhombic Amm2 phase for all compositions, while an orthorhombic Pbcm secondary phase was found for increasing the concentration of MgNb2 O6 . Our results show that densification of these ceramics can be significantly improved up to 94.9 % of theoretical density by adding a small amount of magnesium‐based oxide (1 wt.%). Scanning electron microscopy morphology of the 1 wt.% system reveals a well‐packed structure with homogeneous grain size of ∼2.72 μm. Dielectric and piezoelectric properties become optimal for 0.5–1.0 wt.% of MgNb2 O6 that shows, with respect to the unmodified composition, either higher piezoelectric coefficients, lower anisotropy and relatively low piezoelectric losses (d33 =97 pC N −1 ; d31 =−36.99 pC N −1 and g31 =−14.04×10 −3 mV N −1 ; Qp (d31 )=76 and Qp (g31 )=69) or enhanced electromechanical coupling factors (kp =29.06 % and k31 =17.25 %). Abstract : Piezoceramics K0.5 Na0.5 NbO3 (KNN) have been fabricated with increasing amounts of MgNb2 O6 (MN). The synthesis approach involves a combination of mechanochemical‐assisted activation method and air sintering. The addition of MN reduces the size of grain, improve the density and increase the crystalline disorder of KNN. Furthermore, an increase in the piezoelectric response is found between 0.5–1 wt.% of MN.